2021
DOI: 10.1212/wnl.0000000000011990
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Pregnancy and Puerperium

Abstract: Objective:To investigate whether previously reported increasing incidence of pregnancy-associated stroke (PAS) is observed in chart-validated register data in Finland. In an exploratory analysis, we studied risk factors for PAS.Methods:We performed a retrospective population-based cohort study and nested case-control study in Finland 1987-2016. The Medical Birth Register (MBR) was linked with the Hospital Discharge Register to identify women with incident stroke (ischemic stroke, cerebral venous thrombosis, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 39 publications
4
61
2
1
Order By: Relevance
“…The literature search identified eight studies. Three were from the Nationwide Inpatient Sample in the US ( 12 14 ), two were national healthcare register-based studies from Canada ( 15 ), and one each were from the UK ( 18 ), Sweden ( 19 ), and Finland ( 16 ). One study on temporal trends of severe maternal morbidity in Canada ( 20 ) was excluded as it analyzed the same dataset and time period as the study specifically focused on PAS ( 15 ).…”
Section: Incidence Trends Of Pregnancy-associated Strokementioning
confidence: 99%
See 4 more Smart Citations
“…The literature search identified eight studies. Three were from the Nationwide Inpatient Sample in the US ( 12 14 ), two were national healthcare register-based studies from Canada ( 15 ), and one each were from the UK ( 18 ), Sweden ( 19 ), and Finland ( 16 ). One study on temporal trends of severe maternal morbidity in Canada ( 20 ) was excluded as it analyzed the same dataset and time period as the study specifically focused on PAS ( 15 ).…”
Section: Incidence Trends Of Pregnancy-associated Strokementioning
confidence: 99%
“…Nevertheless, the incidence was lower than in the earlier studies from the US. A recent Finnish population-based study that covered a 30-year time period from 1987 to 2016 revealed an increasing incidence of PAS from 11.1 to 25.2 per 100 000 deliveries from 1987–91 to 2012–16 ( p < 0.0001) ( 16 ). Among stroke subtypes, the rising trend was significant for ischemic stroke and CVT but not for subarachnoid hemorrhage (SAH) or ICH.…”
Section: Incidence Trends Of Pregnancy-associated Strokementioning
confidence: 99%
See 3 more Smart Citations